Pengaruh work life balance dan motivasi kerja terhadap kinerja karyawan dengan kepuasan kerja sebagai variabel intervening - Wahyudin, Ahmad; Fitriati, Azmi; Darmawan, Akhmad; Rachmawati, Erny (Universitas Widya Mataram, 2025)
This study aims to examine the effect of work life balance, and work motivation on employee performance with job satisfaction as a mediating variable. This study is quantitative using primary data taken by distributing questionnaires via Google Form. The population in this study was 235 people. The sample collection technique used purposive sampling technique with the criteria of civil servants and a minimum work period of more than 1 year so that a research sample of 192 people was obtained. The analysis tool used in this study was SEM-PLS. The results of this study indicate that work life balance and work motivation have a positive effect on employee performance and job satisfaction. Job satisfaction has a positive effect on employee performance. And job satisfaction can mediate the effect of work life balance and work motivation on employee performance. The R² value of 47% shows that the employee performance variable can be explained by the variables in this study. The implication based on the research conducted is that the company must always maintain employee work life balance in order to provide employee satisfaction while working and provide good performance. In addition, the company is also expected to be able to provide work motivation to employees so that they can work optimally to achieve common goals.